The Phylogenetic Relationship Revealed Three New Wood-Inhabiting Fungal Species From Genus Trechispora - Wei Zhao; Wei Zhao; Chang-Lin Zhao; Chang-Lin Zhao (Frontiers in Microbiology, 2021)
Wood-inhabiting fungi play a significant role in wood degradation and the cycle of matter in the ecological system. In the present study, three new wood-inhabiting fungal species, Trechispora bambusicola, Trechispora fimbriata, and Trechispora fissurata spp. nov., are nested in Trechispora, which are proposed based on a combination of morphological features and molecular evidence. Sequences of internal transcribed spacer (ITS) and large subunit (nLSU) regions of the studied samples were generated, and the phylogenetic analyses were performed with maximum likelihood, maximum parsimony, and Bayesian inference methods. The phylogenetic analyses inferred from ITS showed that T. bambusicola was sister to Trechispora stevensonii, T. fimbriata grouped with Trechispora nivea, and T. fissurata grouped with Trechispora echinospora. The phylogenetic tree based on ITS + nLSU sequences demonstrated that T. bambusicola formed a single lineage and then grouped with Trechispora rigida and T. stevensonii. T. fimbriata was sister to T. nivea. T. fissurata grouped with Trechispora thelephora.